2014
DOI: 10.1016/j.jcat.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The reaction network in propane oxidation over phase-pure MoVTeNb M1 oxide catalysts

Abstract: MoVTeNb oxide catalysts exclusively composed of the M1 phase (ICSD no. 55097) have been studied in the direct oxidation of propane to acrylic acid applying a broad range of reaction conditions with respect to temperature (623-633-643-653-663 Highlights• Phase purity and homogeneity ensure high stability of MoVTeNbO x in C 3 H 8 oxidation• The catalyst bears a self-supported active layer in sub-nanometer dimension• Higher O 2 content in the feed increases the activity without loss of selectivity• Oxygen part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 65 publications
(90 reference statements)
11
96
1
3
Order By: Relevance
“…For example, V +5 /V +4 pairs are claimed to be responsible for active lattice oxygen in most publications [11,[25][26][27]50,76] but changes in oxidation states of Mo, Te(Sb), and Nb are debated based on techniques used (XPS vs. XANES/EXAFS, etc.) and the type of oxidation reactions [11,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, V +5 /V +4 pairs are claimed to be responsible for active lattice oxygen in most publications [11,[25][26][27]50,76] but changes in oxidation states of Mo, Te(Sb), and Nb are debated based on techniques used (XPS vs. XANES/EXAFS, etc.) and the type of oxidation reactions [11,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion was later supported by in situ XRD studies which showed the remarkable stability of the bulk structure with no indication for segregation of any phases. However, the morphology of the M1 particles is damaged after prolonged periods due to reduction and evaporation of Te [76]. A debate remains in the literature surrounding the nature of the surface restructuring process and identifying Extensive in situ/operando XPS and XRD studies were performed by the same group in other papers to analyze the surface and bulk catalyst compositions/structures during the propane oxidation reaction [17,75,76].…”
Section: Selective Oxidation Of Propane To Acrylic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…4, 5 The multiple catalytic functions of the M1 phase capable of activating various functional groups (e.g., alkanes, alkenes, alcohols, aldehydes) are considered a key aspect that enables the direct formation of acrylic acid with high selectivity 6. 7 Structural assignment of the catalytic functions is not straightforward, as the catalytic functions of M1 are closely related to the dynamics of the M1 surface changes in response to the reaction atmosphere (e.g., gas composition, temperature) 810. It is likely that the gradient of the gas composition within the catalyst bed influences the catalytic properties of M1.…”
Section: Methodsmentioning
confidence: 99%